'Because we must not forget': thematic reading of WWII diaries of young women and girls. Issue 2 (3rd April 2018) - Rudin, Shai
ABSTRACT: This article presents a feminist thematic reading of three diaries written by young women and girls during World War II. The diaries were written by Anna Frank, Hélène Berr, and Ruth Maier, and have not yet been comparatively studied. The thematic reading presented here has focused on four super-themes characterizing the diary-keeping of women during the Holocaust – love, writing, war, and the status of women.